Crossing Borders - Yousef, Bilal (Israel : Hagar Kot Film Productions, 2007)
“Crossing Borders” tells the story of Aisha Sidawi and Umiya Abu-Ras, two Palestinian Israeli women struggling to achieve equality with the men in their lives. They are taking part in political activities an area that used to be for “men only”, and are struggling to cross both personal and political boundaries. In their efforts - the personal one at their homes with family members, and the political one with their Palestinian community in Israel as well as with the Palestinian authorities – they fortify and support each other.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films